Results of the Seventh Scientific Workshop of ECCO: Precision Medicine in IBD—Disease Outcome and Response to Therapy - Verstockt, Bram; Noor, Nurulamin M; Marigorta, Urko M; Pavlidis, Polychronis; Deepak, Parakkal; Ungaro, Ryan C (Journal of Crohn's and colitis, 2021)
Abstract Inflammatory bowel diseases [IBD] are a heterogeneous spectrum with two extreme phenotypes, Crohn’s disease [CD] and ulcerative colitis [UC], which both represent numerous phenotypical variations. Hence, we should no longer approach all IBD patients similarly, but rather aim to rethink clinical classifications and modify treatment algorithms to usher in a new era of precision medicine in IBD. This scientific ECCO workshop aims to provide a state-of-the-art overview on prognostic and predictive markers, shed light on key questions in biomarker development, propose best practices in IBD biomarker development [including trial design], and discuss the potential for multi-omic data integration to help drive further advances to make precision medicine a reality in IBD.